Synthesis and Modification of Macroporous Titania using Silver Nanoparticles - Natalita Maulani Nursam; Jeannie Ziang Yie Tan (Chemistry Department, The University of Brawijaya, 2018)
A synthesis method for preparing macroporous nitrogen and silver-modified titania via sol-gel route is presented. The addition of nitrogen and silver nanoparticles was carried out simultaneously with a hard templating technique using silica spheres packed into a three dimensional opal structure. The influence of such modifications on the optical and chemical properties of titania was evaluated using photocatalytic degradation under visible light. The macroporous opal templated samples in this work performed better than the commercial titania, Degussa P25. The highest photocatalytic enhancement, showing more than eight times higher activity than the non-modified titania, was achieved by the opal templated sample prepared with 1.0 mol % of silver. Although silver addition and macroporous templating enhanced the visible light activity, the most significant improvement was afforded by the utilization of the silica opal template that gave rise to high surface area (>100 m2 g-1) and promoted the surface charge interaction.